Effect of redox agents on the reaction behavior of pyrite in sodium aluminate solution at elevated temperatures. (January 2023) - Wang, Saikui; Wang, Yilin; Qi, Tiangui; Liu, Guihua; Zhou, Qiusheng; Peng, Zhihong; Niu, Fei; Li, Xiaobin
Graphical abstract: Highlights: Inhibiting pyrite decomposition by adding oxidant in Bayer process. Adding NaNO3 to form a dense layer on surface of pyrite particles. Verifying the inhibition of pyrite reaction in an actual bauxite. Abstract: As the main sulfide mineral in diasporic bauxite, pyrite readily reacts with sodium aluminate solution in Bayer digestion at elevated temperatures, adversely affecting the utilization of high-sulfur bauxite for alumina production by the Bayer process. For better understanding of the reaction mechanism during Bayer digestion, this paper focuses on the impacts of oxidant and reductant on the reaction extents of pyrite at elevated temperatures. The extents of reaction between pyrite and sodium aluminate solution are 57.9, 38.3 and 99.0 % at 260 °C for 40 min with no, oxidant and reductant addition, respectively. In the presence of oxidant, a dense layer formed on the surface of unreacted pyrite retarding the reaction with sodium aluminate solution, which follows the Kröger and Ziegler diffusion control model at 240–260 °C. However, the presence of reductant favors the decomposition of pyrite due to the formation of hematite and then transformation to magnetite, and the development of "chemical etching channel". Finally, the above results were experimentally verified by digesting high-sulfur diasporic bauxite at 260 °C for 60 min, in which the inhibition of pyrite reaction with oxidant addition is affected by the organic content of the bauxite. These results may facilitate the development of a technique for directly treating the high-sulfur diasporic bauxite for alumina production with the Bayer process bypassing desulfurization pretreatment.